Tomorrow's economy : a guide to creating healthy green growth - Stoknes, Per Espen (MIT Press, 2021)
A balance sheet for the planet: How we can achieve healthy growth more regenerative than wasteful, instilling equity rather than exacerbating inequalities. In Tomorrow's Economy, Per Espen Stoknes reframes the hot-button issue of economic growth. Going beyond the usual pro-growth versus anti-growth debate, Stoknes calls for healthy growth. Healthy economic growth is more regenerative than wasteful, repairs problems rather than greenwashing them, and restores equity rather than exacerbating inequalities. Stoknes a psychologist, economist, climate strategy researcher, and green-tech entrepreneur shows that we already have the tools to achieve healthy growth, but our success depends on transformations in scaling innovations, government practices, and individual behaviors. Stoknes provides a compass to guide us toward the mindset, mechanisms, and possibilities of healthy growth. Stoknes explains that healthy growth reimagines value creation as resource smart and inclusive. Healthy growth is measurably profitable, more resource-productive, and more redistributive by design each year. Stoknes distinguishes between healthy and unhealthy kinds of economic growth at personal, corporate, city, national, and global levels, mapping a three-part synergy that benefits buyers, sellers, and society. He outlines actions we can take now including the creation of a new legal entity, the benefit corporation and lays out six steps companies can take toward healthy growth. He also describes how we can vote with our wallets to prioritize sustainability. The engaged citizen, he tells us, is central to the shift toward healing growth.- Resumé vydavatel
Keywords: ekonomický růst -- environmentální aspekty; udržitelný rozvoj -- psychologické aspekty; economic development -- environmental aspects; sustainable development -- psychological aspects; elektronické knihy; monografie; electronic books; monographs